Inward rectification in frog skeletal muscle fibres and its dependence on membrane potential and external potassium. - Leech, C A (1981)
1. Experiments were carried out using a voltage-clamp technique to investigate the dependence of inward rectification on membrane potential and on the equilibrium potential for K+, changed either by changing [K]o or changing [K]i. 2. The relationship between gK, the potassium chord conductance, and membrane potential depended on membrane potential and [K]o, but not on [K]i. 3. Under hyperpolarization, K currents increased with time, but instantaneous current-voltage relations also showed inward rectification. The time constants for activation fell with hyperpolarization, e -fold for an 18 mV change in membrane potential. 4. The time constants for activation depended on [K]o but not on [K]i. 5. Under depolarization, the activation of K currents was partly reversed, but between activation and membrane potential, determined from two-pulse experiments, also appeared to depend on [K]o but not on [K]i. 5. Under depolarization, the activation of K currents was partly reversed, but between activation and membrane potential, determined from two-pulse experiments, also appeared to depend on [K]o but not on [K]i. 6. The rate of activation of K currents under hyperpolarization had a Q10 of 2.64 +/- 0.08 (n = 5). Currents, measured per unit length, increased with temperature, with a Q10 of 1.66 +/- 0.11 (n = 5).